Основні смисли портрета як артефакту культури - Успенський, Володимир; Uspenskyi, Vîlodymyr (ТНЕУ, 2011)
До основних смислів портрета (портрет - пам’ятник моделі і художникові й одночасно носій візуальної інформації) віднесено художню ідею. У результаті дослідження смислу портрета як пам’ятника доведено, що, незважаючи на кризу портретного жанру, він існуватиме і в майбутньому. Сформульована гіпотеза про прадавні витоки портретного мистецтва, виявлено існування діалектичної єдності двох протилежних смислів портрета: прадавнього - портрет як “знаряддя зла”, і сучасного - портрет як “знаряддя добра”. To basic senses of portrait (a portrait is monument to model and monument to artist and at the same time the portrait is a carrier of visual data) an author attributed an artistic idea. As a result of research of sense of portrait as monument the author came to the conclusion, that, in spite of crisis of genre of portrait, a portrait will exist and in the future. The hypothesis was formulated about the most ancient origins of the art of portrait. The author has shown the existence of dialectical unity of two opposite senses of portrait: most ancient - portrait is an “instrument of evil” and modern – a portrait is an “instrument of good”.
The main meanings of portrait as the artifact of culture
Keywords: культура; особистість; портрет; смисл; артефакт; пам’ятник; носій візуальної інформації; трансляція смислів; добро; зло; portrait; sense; artifact; monument; carrier of visual data; translation of senses; good; evil